Strategi Komunikasi Yayasan Rumah Tahfidz Yatim Dhuafa (RTYD) dalam Menarik Minat Pengunjung di Destinasi Edukasi dan Wisata Al-Qur’an Kota Palembang (Desa Qur’an) - Rahayu, Tri; Sihabudin, Amin; Muslimin (Pubmedia Social Sciences and Humanities, 2024)
This research is aimed at managing tourist destinations and locations which aim to attract visitor interest, considering that the tourist location called 'Qur'an Village' has recently been inaugurated so it is necessary to disseminate information and compare it to the public both inside and outside the city of Palembang. The purpose of this research is to find out and understand the communication strategies implemented by Rumah Tahfidz Yatim Dhuafa when creating opportunities and to find out the factors that hinder both the management and communication strategies used. This research uses a qualitative research method in the form of descriptive data results both through a process of data collection through observation, interviews, documentation stages, obtained from primary and secondary data. The results of this research show that the communication strategy for attracting visitor interest at Al-Qur'an Education and Tourism Destinations uses the Five Step Theory which consists of stages: Research, Planning, Implementation, Evaluation and Reporting. Meanwhile, in the execution process, the management also uses social media to facilitate access to information for the general public, both from tourist locations to tourism products.